KAJIAN EMPIRIS AUDIT JUDGEMENT PADA AUDITOR - Yustrianthe, Rahmawati Hanny (Media Riset Akuntansi, 2012)
This  study  examines  the  factors  that  influence  on  audit  judgement  (i.e.  gender,  obedience pressure,  task  complexity,  and  experience).This  study  used  auditors  Badan  Pemeriksa Keuangan  (BPK)  dan  badan  Pengawasan  Keuangan  dan  Pembangunan  (BPKP)  in Jakarta  as  respondent.  Collecting  data  was  conducted  by  questionnaire  distributed  as much  400,  however  only  210  (52,5%)  questionnaires  replayed.  Data  were  analyzed  by multiple  regression  method.  The  result  of  research  showed  that  the  obedience  pressure and  task  complexity  affects  audit  judgement.  However,  gender  and  experience  didn’t affect  audit  judgement. Keywords: gender,  obedience  pressure,  task  complexity,  experience,  audit  judgement